O grupo cervejeiro nacional petrópolis na evolução do capitalismo brasileiro: concorrência e expansão territorial - Marcusso, Eduardo Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The processes resulting from globalization are backdrop for the work. On the other hand the Regulation Theory is theoretical north that drives research directions. Considering these two basis, we studied the formation of economic groups as a consequence of the processes of concentration and centralization of capital, giving more emphasis on their national character. We see how they went through the restructuring process in the transition from Fordist accumulation regime to a flexible system of accumulation. We 'll discuss the brewery industry and how major industry groups are currently creating a sector overview, ranging from the productive process to the forms of competition among large companies. Specifically we will see the Petrópolis Group this framework and how the company relates to the territory, and what answers we have of this relationship in terms of local development in the territories where the group entered, and territorial changes which have occurred there

Os processos decorrentes da globalização são o pano de fundo do trabalho. Já a Teoria da Regulação é norte teórico que guia os rumos da pesquisa. Considerando esses dois alicerces, estudamos a constituição dos grupos econômicos como conseqüência dos processos de concentração e centralização do capital, dando mais ênfase no seu caráter nacional. Vemos como eles passaram pela reestruturação produtiva na transição do regime de acumulação fordista para um sistema flexível de acumulação. Trataremos do setor cervejeiro e como os grandes grupos do setor se encontram atualmente, montando um panorama do setor, que vai desde o processo produtivo até as formas de concorrência entre as grandes empresas. Especificamente veremos o Grupo Petrópolis neste enquadramento e de que maneira a empresa se relaciona com o território, e que respostas temos dessa relação, em termos de desenvolvimento local nos territórios onde o grupo se inseriu, e quais as transformações territoriais ali ocorridas
Keywords: Grupo Petrópolis; Geografia econômica; Cerveja - Comercio; Concorrência; Globalização - Aspectos econômicos; Produção (Teoria economica); Grupo de interesse econômico; Boituva (SP); Economic geography; Beer industry; Competition; Globalization - Economic aspects; Production (Economic theory); Economic interest groupings